2013
DOI: 10.1002/anie.201300896
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐free Direct Growth of a Single to a Few Layers of Graphene on a Germanium Nanowire for the Anode Material of a Lithium Battery

Abstract: Direct growth of a single to a few layers of graphene on a germanium nanowire (Gr/Ge NW; see picture) was achieved by a metal-catalyst-free chemical vapor deposition (CVD) process. The Gr/Ge NW was used as anode in a lithium ion battery. This material has a specific capacity of 1059 mA h g(-1) at 4.0 C, a long cycle life over 200 cycles, and a high capacity retention of 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 33 publications
1
87
0
2
Order By: Relevance
“…14,15 Despite of these superior properties, however, an electrode based on pure Ge exhibits poor performance because of its dramatic capacity decay caused by large volume change during the lithiation and delithiation processes. 16,17 Several approaches have been proposed to buffer the volume change, such as carbon nanotube (CNT)/Ge nanoparticles core/shell structure, 18 Cu nanowire/Ge nanoparticles, 19 Ge nanowire/graphene, 20,21 Ge nanoparticle/graphene (carbon), 14,[22][23][24] Si/Ge bilayer nanotubes, 25 nanostructured Ge films, 26 and Ge nanoparticles-reduced graphene oxide (RGO) composites. [27][28][29] Among them, it was found that compositing Ge with a carbon shell can effectively moderate its kinetic properties toward electron and Li ion transport, and the carbon shell also acts as a cushion in alleviating the internal stress induced upon volume change, preventing cracking, pulverization, and aggregation of Ge electrode.…”
Section: Ion Batteriesmentioning
confidence: 99%
“…14,15 Despite of these superior properties, however, an electrode based on pure Ge exhibits poor performance because of its dramatic capacity decay caused by large volume change during the lithiation and delithiation processes. 16,17 Several approaches have been proposed to buffer the volume change, such as carbon nanotube (CNT)/Ge nanoparticles core/shell structure, 18 Cu nanowire/Ge nanoparticles, 19 Ge nanowire/graphene, 20,21 Ge nanoparticle/graphene (carbon), 14,[22][23][24] Si/Ge bilayer nanotubes, 25 nanostructured Ge films, 26 and Ge nanoparticles-reduced graphene oxide (RGO) composites. [27][28][29] Among them, it was found that compositing Ge with a carbon shell can effectively moderate its kinetic properties toward electron and Li ion transport, and the carbon shell also acts as a cushion in alleviating the internal stress induced upon volume change, preventing cracking, pulverization, and aggregation of Ge electrode.…”
Section: Ion Batteriesmentioning
confidence: 99%
“…18 Strategies to mitigate these problems generally involve nanostructuring the Ge to minimise volume swing, and embedding it on an electrically conducting scaffold such as amorphous carbon or reduced graphene oxide to buffer against mechanical instability and enhance the rate capability. 5 Recently "coreshell structure" such as Ge NWs (core)/carbon (shell) as a generic concept has emerged as a favored material design in energy storage system. 5 Recently "coreshell structure" such as Ge NWs (core)/carbon (shell) as a generic concept has emerged as a favored material design in energy storage system.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ge nanostructures tend to have a lower density, leading to a small volumetric capacity. Second approach was to introduce a buffering matrix to coat Ge [10][11][12] or to be coated by Ge [13], Ge composite [14], etc. Depending on the ratio of active Ge to the buffer matrix, the theoretical specific capacity of the composite might be significantly decreased.…”
Section: Introductionmentioning
confidence: 99%